THE SPARTAKIADE AS A PHENOMENON IN THE SOCIO-CULTURAL AND SPORTS DIMENSION IN THE TERRITORY OF CZECHOSLOVAKIA - Michal Bábela; Josef Oborný (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
The aim of the article is to provide a description of the emergence and genesis of the Spartakiade in the territory of former Czechoslovakia. In the article, we focused on the origin and development of mass sport in Czechoslovakia since 1918, on the emergence and genesis of the Spartakiade and the definition of the term "Spartakiade". In this paper, we also present a chronological name list and a brief course of individual Spartakiades that were held in the territory of Czechoslovakia within the period 1955 - 1985.